Th1/Th2 cytokines and ICAM–1 levels post-liver transplant do not predict early rejection. Issue 1 (2000) - Granot, E.; Tarcsafalvi, A.; Emre, S.; Sheiner, P.; Guy, S.; Schwartz, M. E.; Boros, P.; Miller, C. M.
Abstract : Th1 derived cytokines IFN-γ and IL–2, Th2 cytokine IL–4, and ICAM–1 have been implicated in liver allograft rejection. In order to determine whether monitoring of cytokine profiles during the first days post-liver transplant can predict early rejection we measured IFN-gg, IL–2, sIL–2 receptor, IL–4 and ICAM–1 in 22 patients, in plasma samples obtained within 4h after liver perfusion (baseline) and between postoperative days (POD) 3–6. ICAM–1 and sIL–2R levels at POD 3–6 were significantly higher than at baseline but did not differ in presence or absence of rejection. Mean percentage increase of ICAM–1 levels was significantly lower in patients with Muromonab-C3 Orthoclone OKT3 (J.C. Health Care) (OKT3 ) whereas percentage increase of sIL–2R levels was higher in OKT3 -treated patients. IFN-γ levels at POD 3–6 increased from baseline while IL–4 levels were unchanged. Levels of IFN-γ, IL–4 and their ratios did not correlate with rejection or immunosuppressive therapy. Thus, Th1 /Th2 cytokine monitoring during the first week post-transplant does not predict early rejection and immunosuppressive therapy is the predominant factor affecting ICAM and sIL–2R levels after liver transplantation.